Essential counseling skills : practice and application guide - Magnuson, Sandra L., ....-; Norem, Ken., ....- (Thousand Oaks (Cal.) : SAGE Publications, Inc., 2014)
Essential Counseling Skills: Practice and Application Guide offers practical, step-by-step guidance for developing and applying the skills necessary for careers in counseling. Using the metaphor of a professional journey, this guide provides commentary and background information throughout, as readers are directed in their development of such key counseling skills as empathy, building relationships, case conceptualization, and facilitating change. Deep reflection is further encouraged at every key stage through the integration of theory with a wealth of applied exercises and examples.
Preface -- Acknowledgments -- Introduction -- Tour 1: Preparation for departure : who am I and how do I interact with others? -- Tour 2: Preparation for departure : building relationships with basic listening skills -- Tour 3: Departure : advanced facilitation skills -- Tour 4: Traveling with a theory : integration and personalization -- Tour 5: Applying theory : assessment and conceptualization -- Tour 6: Meeting clients : treatment planning, progress monitoring, and documentation -- Tour 7: Consolidation : celebrating the journey and preparing to go our separate ways -- Index -- About the authors.
Includes bibliographical references and index.
Keywords: Counseling -- Handbooks, manuals, etc; Counseling; Hulpverlening